A területi egyenlőtlenségeket és a versenyképességet meghatározó társadalmi tényezők Hajdú-Bihar megye térségeiben - Bánfalvi Győző Sándor; Czibere Ibolya (Belvedere Meridionale Szeged, 2020)
The general approach of an area’s social and economic change is often the result of a quantitative assessment of one of its sectors. However, the processes that have taken place can be better captured through a complex index that carries the major economic and social characteristics of the observed area. By compiling such a complex social and economic index we characterize the competitiveness of a region, and regional rankings compiled on the basis of such complex territorial indicators also helped to allocate EU funds in Hungary. One of the aims of our study is to try to determine the movement of Hajdú-Bihar County and its regions on the map of the relative territorial inequality of the country from the change of regime to the end of the fi rst EU development cycle. We could do this in two major periods. In the fi rst, we examined the period from the change of regime to Hungary’s joining the EU with the help of the categorization of the competitiveness of the regions in Hungary. In the second period we can follow the development of the territorial inequality in Hungary during the fi rst EU development cycle. This observation is based on the values of complex social and economic indicators recorded at the start and the end of this period, and the regional rankings established on the basis of them. During the whole period examined only little change could be detected in the relative rankings of the counties. For example, Hajdú-Bihar County was the sixth worst-hit Hungarian county in 2007, and at the start of the new EU development cycle (2013) it fell back by one position. Meanwhile, the large territorial inequalities that had previously characterized the country remained and even increased. These are refl ected in the increase of territorial inequalities within the counties, thus the territorial inequalities of Hajdú-Bihar County also increased signifi cantly. The whole period in study is characterized by the growth of territorial inequality, but its tendency is not the same. The polarization within the county started right after the regime change, then accelerated and intensifi ed signifi cantly during the periods. Another important objective of our study is to try to interpret the tendencies in relation to the territorial inequality of Hajdú-Bihar county directly through the change of county-level competitiveness factors.
Keywords: Társadalomtudományok; Társadalom- és gazdaságföldrajz